FaCT2 Study Protocol: A Randomized, Controlled Trial Exploring Cognitive Training to Reduce Risk of Falls in at Risk Older Adults - Thompson, Hilaire J. (Inj Prev, 2019)
BACKGROUND: The primary cause of traumatic injury in older adults is fall. Recent reports suggest that cognitive function contributes significantly to fall risk. Therefore, by targeting cognitive function for intervention, we could potentially reduce the incidence of fall and injury. PRIMARY OBJECTIVE: To explore the effectiveness of a 16-week cognitive training (CT) intervention to reduce risk and incidence of fall in community-dwelling older adults at risk for fall. OUTCOMES: Primary outcome is number of falls over a 16-week period (ascertained by fall calendar method). Secondary outcomes include: change fall risk as indicated by improvement in 10M walk and 90-second balance tests. DESIGN/METHODS: The design is a two-group, randomized controlled trial. Eligible participants are older adults (aged 65–85) residing in the community who are at risk for fall based on physical performance testing. Following completion of 1-week run-in phase, participants are randomly allocated (1:2) to either a group that is assigned to attention control or to the group that receives CT intervention for a total of 16 weeks. Participants are followed for an additional 4 weeks post-intervention. Mann-Whitney U and Student’s t-tests will be used to examine between group differences using intention-to-treat analyses. DISCUSSION: Limited evidence supports the potential of CT to improve cognition and gait, but no published study has evaluated whether such an intervention would reduce incidence of fall. The present trial is designed to provide initial answers to this question. CT may also improve functioning important in other activities (e.g. driving), reducing overall risk of injury in elders.